Analysis of the monthly rainfall in 2018-2019 in Palembang City and its relationship with climate conditions - Novtriana, Deasti; Kurniawati, Netty; Hadi, Hadi; Koriyanti, Erry; Saleh, Khairul; Sutopo, Sutopo; Safrina, Sri; Awaludin, Awaludin; Irfan, Muhammad (Faculty of Mathtmatics and Natural Sciences, 2023)
The amount of monthly rainfall can be classified into wet months, humid months, and dry months. The number of wet months, humid months, and dry months is related to the climatic conditions in the year concerned. In 2018 there was no climate anomaly (deviation), but in 2019 there was a climate anomaly due to the Positive Indian Ocean Dipole (IOD+) natural phenomenon. This study calculates the number of wet months, moist months, and dry months that occurred in 2018 and 2019 in Palembang City and relates them to the climatic conditions in both years. The data used is the amount of rainfall measured from 2 measurement stations, namely the UNSRI Bukit Besar station and the BMKG Kenten Palembang. The results of this study indicate that in both years for the city of Palembang, there were wet months, humid months. and dry months. In the dry months of 2019, especially in August and September, the amount of rainfall is very minimal, even in August there is almost no rain. This happened because in 2019 there was a climate anomaly related to the Positive Indian Ocean Dipole (IOD+) natural phenomenon.